UHPLC-MS/MS method for analysis of sobuzoxane, its active form ICRF-154 and metabolite EDTA-diamide and its application to bioactivation study - Reimerová, Petra; Jirkovská, Anna; Piskáčková, Hana Bavlovič; Karabanovich, Galina; Roh, Jaroslav; Šimůnek, Tomáš; Štěrbová-Kovaříková, Petra (Scientific reports, 2019)
Sobuzoxane (MST-16) is an approved anticancer agent, a pro-drug of bisdioxopiperazine analog ICRF-154. Due to the structural similarity of ICRF-154 to dexrazoxane (ICRF-187), MST-16 deserves attention as a cardioprotective drug. This study presents for the first time UHPLC-MS/MS assay of MST-16, ICRF-154 and its metabolite (EDTA-diamide) in cell culture medium, buffer, plasma and cardiac cells and provides data on MST-16 bioactivation under conditions relevant to investigation of cardioprotection of this drug. The analysis of these compounds that differ considerably in their lipophilicity was achieved on the Zorbax SB-Aq column using a mixture of aqueous ammonium formate and methanol as a mobile phase. The biological samples were either diluted or precipitated with methanol, which was followed by acidification for the assay of MST-16. The method was validated for determination of all compounds in the biological materials. The application of the method for analysis of samples from in vitro experiments provided important findings, namely, that (1) MST-16 is quickly decomposed in biological environments, (2) the cardiac cells actively metabolize MST-16, and (3) MST-16 readily penetrates into the cardiac cells and is converted into ICRF-154 and EDTA-diamide. These data are useful for the in-depth examination of the cardioprotective potential of this drug.
Keywords: razoxan; Animals; Edetic Acid; Rats, Wistar; Myocytes, Cardiac; piperaziny; Tandem Mass Spectrometry; vysokoúčinná kapalinová chromatografie; EDTA; Antineoplastic Agents; protinádorové látky; kultivované buňky; Cells, Cultured; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Piperazines; kardiomyocyty; krysa rodu Rattus; zvířata; Razoxane; Rats; potkani Wistar